Nasopharyngeal carriage of Streptococcus pneumoniae in Latin America and the Caribbean: A systematic review and meta-analysis - Brizuela, Martín (2024)
Background: Streptococcus pneumoniae is a leading cause of morbidity and mortality globally, causing bacteremic pneumonia, meningitis, sepsis, and other invasive pneumococcal diseases. Evidence supports nasopharyngeal pneumococcal carriage as a reservoir for transmission and precursor of pneumococcal disease.Objectives: To estimate the pneumococcal nasopharyngeal burden in all age groups in Latin America and the Caribbean (LAC) before, during, and after the introduction of pneumococcal vaccine conjugate (PVC).Methods: Systematic literature review of international, regional, and country-published and unpublished data, together with reports including data from serotype distribution in nasopharyngeal carriage in children and adults from LAC countries following Cochrane methods. The protocol was registered in PROSPERO database (ID: CRD42023392097).Results: We included 54 studies with data on nasopharyngeal pneumococcal carriage and serotypes from 31,803 patients. In children under five years old, carriage was found in 41% and in adults over 65, it was 26%. During the study period, children under five showed a colonization proportion of 34% with PCV10 serotypes and 45% with PCV13 serotypes. When we analyze the carriage prevalence of PCV serotypes in all age groups between 1995 and 2019, serotypes included in PCV10 and those included in PCV13, both showed a decreasing trend along analysis by lustrum.Conclusion: The data presented in this study highlights the need to establish national surveillance programs to monitor pneumococcal nasopharyngeal carriage to monitor serotype prevalence and replacement before and after including new pneumococcal vaccines in the region. In addition, to analyze differences in the prevalence of serotypes between countries, emphasize the importance of approaches to local realities to reduce IPD effectively.